Development of An-Nawa Method-Based Learning Module for Basic-Level Quranic Literacy - Maman, Maman; Wahyuddin, Wawan; Hidayatullah, Hidayatullah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
Learning to read and write the Qur'an is fundamental to Islamic religious education. However, existing teaching methods often need to be more effective in meeting diverse learners' needs. It encourages the development of adaptive modules that meet the needs of students, such as the An-Nawa module, which adapts the Iqra and Ummi methods. This study aims to create an adaptation of the An-Nawa Module of Iqra and Ummi and assess how well it works. The research methodology employs the ten-stage Borg and Gall research and development technique. The research and development study's findings indicate that the following principles developed the An-Nawa module: analysis of educational needs, gathering pertinent data, product design that takes students' needs into account, validation demonstrating the module's viability, design revision, testing, product revision, usage testing, product revision, as well as socialization and implementation. These phases are all essential to developing a module, which also involves implementation, assessment, and revision to guarantee the module's viability and efficacy in raising students' proficiency in reading and writing the Al-Qur'an. The suggestions are to do limited testing, involve experts in the development process, and revise the module continuously to raise its quality. To guarantee that the module positively influences students' abilities to read and write the Al-Qur'an, socialization, and module execution are equally crucial.